Determination of limit velocities of supercavitating motion of strikers from various materials in water - Ishchenko, Aleksandr N.; Burkin, Viktor V.; Diachkovskii, Alexei S.; Sammel, Anton Yu; Chupashev, Andrey V. (Journal of engineering physics and thermophysics)
Experimental-theoretical investigations have been conducted into underwater supercavitating motion of cone strikers from various materials in a broad range of velocities. An estimate of the range of strikers' velocities has been performed for the implementation of their nondestructive entry into water and motion in it in a supercavitating regime. A possibility of an accurate hit by supercavitating strikers on underwater barriers in a supersonic range of motion velocities has been shown.